Research Progress on Control Technology of Farmland Runoff Pollution - Yao, Yuxuan; Ye, Shenglan (Scientific Journal of Technology, 2025)
This paper introduces the sources of agricultural runoff pollution and reviews control technologies for agricultural runoff pollution from the perspective of "source control-process interception." It analyzes integrated technology cases in real-world scenarios, using the Taihu Basin in Jiangsu Province and Jiaxing City in Zhejiang Province as examples to illustrate the application effects of the "source control + process interception" and "smart monitoring + dynamic regulation" systems. These integrated technology models have significantly reduced pollutant levels in agricultural runoff and improved water quality in surrounding waters, providing an effective solution for controlling non-point source pollution from agriculture. Current ecological measures still face challenges such as insufficient long-term effectiveness and technical-economic conflicts. To address these issues, it is recommended to innovate modular technologies, implement policy mechanisms, establish an integrated mechanism for infrastructure construction, management, and utilization through diversified funding mechanisms, and build intelligent platforms to enhance system efficiency. Ultimately, a three-step strategy of "pilot breakthrough-regional promotion-national networking" will achieve large-scale, intelligent, and sustainable governance of agricultural non-point source pollution.